Evaluation of the effect of containers on the seismic response of pile-supported storage structures. (1st September 2016) - Reyes, Juan C.; Ardila-Bothia, Luis; Smith-Pardo, J. Paul; Villamizar-Gonzalez, J. Nicolás; Ardila-Giraldo, Oscar A.
Highlights: Portion of live load as seismic mass can be estimated experimentally. Squat live load objects contribute more to seismic drift demands than slender blocks. Less energy may be dissipated through sliding as compared to rocking of blocks. Codes may underestimate the effective live load as inertia for service-level shaking. Maximum floor acceleration correlates well with portion of live load as inertia. Abstract: In order to evaluate the effect of containers on the dynamic response of a pile-supported storage structure, this paper presents results of 154 shake table tests conducted using a 1:15 scale single story model that supported a block with the possibility to slide and/or rock. The experimental program involved five block-to-structure mass ratios, two block aspect ratios, and two seismic hazard levels. Drift demands on the model were measured to be higher when the structure supported a squat block as compared to a slender block with the same mass. The implementation of a statistical methodology to quantify the effect of the blocks on the seismic response of the one-story laboratory model showed that for the conditions of the experimental program: (a) squat blocks had a larger portion of their mass effectively contributing to inertial forces on the structure as compared to slender blocks; (b) the portion of the block's mass that was effective as inertia does not exhibit a clear correlation with the block-to-structure mass ratio (even though drift demands on the model were consistently higher for heavier blocks); (c) the live load percentages that are prescribed in current codes and standards may significantly underestimate the contribution of live load to inertial forces, especially for service-level ground motions. A design expression previously developed by the authors was favorably compared against the experimental results reported in this paper. Numerical modeling was carried out to extend the conclusions and observations to conditions beyond those of the experimental program.